Are public sector banks in India a government failure? : a comparative empirical analysis of public sector and private sector banks in India - Chopra, Sahil (2022)
To extend banking services to the Indian rural sector, an act was passed in 1976 and then in 1980 to nationalize the banks. Giving the name to such an approach as social banking. Banking sector in India, therefore, has been bifurcated into public sector banks, private sector banks, foreign banks, regional rural banks, urban cooperative banks and rural cooperative banks. Many studies have assessed the performance of private and public sector banks. Such research has evaluated the performance of private and public sector banks by estimating bank-specific and macroeconomic parameters. However, not many quantitative literatures are available which have estimated the impact of ownership on bank performance by considering ownership as one of the bank-specific independent variables to evaluate the impact of ownership on bank profitability. This paper seeks to fill this gap by examining the determinants of profitability on the account of ownership, and it uses an independently constructed dataset containing all commercial public and private sector banks in India as on April 2020. The data ranges from 2004 to 2020. The justification to measure the impact of ownership comes from the theory of Government failure, which mainly points out how government intervention can result in costly solutions. Therefore, by adding the independent variable in an already established model, we can assess the impact of ownership. Banks’ characteristics are collected from respective banks’ websites, and the hypotheses are tested by estimating an econometric model, i.e. a pooled OLS model. The results are promising: the banking industry as a whole is not performing well, however government owned banks are showcasing the worst performances. The reason for this can be the huge amount of loans sanctioned in priority sectors and fraudulent cases which may be due to the presence of interest groups, corruption and inefficiency of employees in public sectors.